The Use of HIS6 Gene as a Selectable Marker for Yeast Vector - I MADE ARTIKA (Bogor Agricultural University, Indonesia, 2009)
The yeast Saccharomyces cerevisiae HIS6 gene has been shown to be functional as a selectable marker for selecting and maintaining a yeast vector in yeast S. cerevisiae host cells. The yeast HIS6 gene encodes an enzyme involved in the yeast histidine biosynthesis. The yeast HIS6 gene was cloned into a yeast expression vector. The resultant recombinant plasmid was introduced into yeast host cells defective in endogenous HIS6 gene. The functionality of the HIS6 gene as a selectable marker was tested by growing transformed cells on selective minimum medium lacking histidine supplementation. Key words: HIS6 gene, selectable marker, vector, transformation, yeast